2021
DOI: 10.1177/10935266211039474
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Assessment of Mucosal Eosinophils in the Gastrointestinal Tract of Children Without Detectable Organic Disease

Abstract: Background Accurate measurements of mucosal eosinophil concentrations in gastrointestinal tracts of healthy children are necessary to differentiate health and disease states in general, and better define eosinophilic gastrointestinal diseases. Study We retrospectively reviewed gastrointestinal biopsies from children with macroscopically normal endoscopies, who, after a minimal follow-up of one year, were not diagnosed with any organic disease. Peak eosinophil concentrations and distributions were assessed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Other previously reported histologic findings include lamina propria eosinophilia (17%) and increased apoptotic bodies (35%), 21 but it is unclear how these two findings were defined. In our cohort, we found the median number of lamina propria eosinophils to be 27 (range: 6–66) which is within the range of expected number of eosinophils in colon biopsy samples from children 56,57 ; more importantly, there were only four cases with eosinophilic cryptitis and none of the biopsies had eosinophilic crypt abscesses.…”
Section: Discussionsupporting
confidence: 74%
“…Other previously reported histologic findings include lamina propria eosinophilia (17%) and increased apoptotic bodies (35%), 21 but it is unclear how these two findings were defined. In our cohort, we found the median number of lamina propria eosinophils to be 27 (range: 6–66) which is within the range of expected number of eosinophils in colon biopsy samples from children 56,57 ; more importantly, there were only four cases with eosinophilic cryptitis and none of the biopsies had eosinophilic crypt abscesses.…”
Section: Discussionsupporting
confidence: 74%
“…While most of these studies used cross‐sectional cohorts of children with obvious functional complaints, in most cases the children were not followed up to ensure that no organic disease developed after endoscopy or that they had no evidence of bacterial ( H pylori infection), parasitic, or systemic disease that might have contributed to the mucosal eosinophilia. Two studies by Hoofien et al (104) and Koutri et al (28) compared children with resolving symptoms with those who had FGIDs, and found no significant differences in peak eosinophil counts. It should be noted however, that other studies have reported higher GI eosinophil counts in the gastric antrum and body of children with FGIDs compared to normal pediatric reference values (24) and in gastric antrum of children with FGIDs compared to healthy controls (25).…”
Section: Statements Summary Of Evidence and Recommendationsmentioning
confidence: 99%
“…The limitation remains that asymptomatic children were not included for ethical reasons. Both studies (28,104), which were international cohorts from countries in Europe and Israel, but did not include cohorts from North America, found geographic variance in peak eosinophil counts. The geographic differences noted within Europe mean that further differences around the world cannot be ruled out which may be another limitation in setting universal standards.…”
Section: Statements Summary Of Evidence and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations